2014
DOI: 10.1161/circheartfailure.114.001564
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Intermittent Low-Level Transcutaneous Electrical Stimulation of Auricular Branch of Vagus Nerve Improves Left Ventricular Remodeling in Conscious Dogs With Healed Myocardial Infarction

Abstract: Background-Vagus nerve stimulation attenuates left ventricular (LV) remodeling after myocardial infarction (MI).Our previous study found a noninvasive approach to deliver vagus nerve stimulation by transcutaneous electric stimulation of auricular branch of vagus nerve. So we hypothesize that chronic intermittent low-level tragus stimulation (LL-TS) could attenuate LV remodeling in conscious dogs with healed MI. Methods and Results-Thirty beagle dogs were randomly divided into 3 groups, MI group (left anterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 40 publications
1
83
1
1
Order By: Relevance
“…When the same stimulation protocol was applied to the left and right tragus of conscious dogs with healed myocardial infarction, tVNS was improved cardiac function, alleviated cardiac fibrosis and attenuated left ventricular remodelling (Wang et al, 2014;Wang et al, 2015). This low-level tVNS reduced the plasma concentration of non-specific inflammatory markers such as C-reactive protein and decreased the expression of various factors which regulate cellular remodelling such as transforming growth factor beta 1 and matrix metalloproteinase 9 (Wang et al, 2014;Wang et al, 2015). A decrease in the concentration of plasma noradrenaline was further observed, suggesting that lowlevel tVNS may decrease sympathetic nerve activity.…”
Section: Cardiac Effects Of Tvnsmentioning
confidence: 98%
See 3 more Smart Citations
“…When the same stimulation protocol was applied to the left and right tragus of conscious dogs with healed myocardial infarction, tVNS was improved cardiac function, alleviated cardiac fibrosis and attenuated left ventricular remodelling (Wang et al, 2014;Wang et al, 2015). This low-level tVNS reduced the plasma concentration of non-specific inflammatory markers such as C-reactive protein and decreased the expression of various factors which regulate cellular remodelling such as transforming growth factor beta 1 and matrix metalloproteinase 9 (Wang et al, 2014;Wang et al, 2015). A decrease in the concentration of plasma noradrenaline was further observed, suggesting that lowlevel tVNS may decrease sympathetic nerve activity.…”
Section: Cardiac Effects Of Tvnsmentioning
confidence: 98%
“…In healthy human volunteers with no history of cardiovascular disease, tVNS on the inner and outer surface of the tragus significantly improved heart rate variability (through a shift in cardiac autonomic activity towards relative parasympathetic/vagal dominance) and caused a significant decrease in muscle sympathetic nerve activity as recorded by microneurography (Clancy et al, 2014). Further evidence that electrical stimulation of the ABVN can elicit a decrease in sympathetic activity comes from a study by Wang et al (2014), where a reduction in plasma noradrenaline concentration was observed following bilateral tragus stimulation in conscious dogs with healed myocardial infarction (Wang et al, 2014). Zhou et al (2016) also showed that in anesthetized dogs, 3 hours of right tragus stimulation significantly attenuated the sinus rate acceleration in response to right stellate ganglion stimulation and decreased activity in the right stellate ganglion.…”
Section: Mechanism Of Action Of Tvns On Cardiac Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, VNS has shown other clinical benefits in diseases such as hypertension and rheumatoid arthritis 14, 22, 33. Recently, VNS has been proposed as a promising therapeutic approach such as heart failure34 and cardiac arrhythmia35 as it provides cardiac autonomic responses such as chronotropic, inotropic, and dromotropic effects 23, 33, 36. For the clinical applications, several VNS factors such as pulse width, current amplitude, number of pulses, interpulse period, and electrode configurations still need to be verified with the physiological effects, though the therapeutic effect has been recognized in preclinical and pilot clinical studies 23.…”
Section: Resultsmentioning
confidence: 99%